2007
DOI: 10.3892/ijo.31.4.893
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase Tie1 is expressed and activated in epithelial tumour cell lines

Abstract: Abstract. The receptor tyrosine kinase Tie1 is expressed primarily in vascular endothelial cells. The receptor has also been detected in epithelial tumours in breast, thyroid and gastric cancers and in tumour cell lines where it appears as a 45 kDa truncated receptor fragment. In this study, we show that in addition to truncated Tie1, breast and colon tumour cell lines express a full-length Tie1 holoreceptor. In contrast to the situation in endothelial cells, Tie1 truncation is not activated by phorbol esters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…Tie-1 and Tie-2 comprise the Tie family of RTKs and share the angiopoietins as activating ligands. Tie-1 is typically expressed on vascular endothelium and has been implicated in tumor angiogenesis [40]. Expression of Tie-1 has been reported in breast, gastric, colon, and thyroid cancers, but constitutive activation has only been proven in a breast cancer cell line [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tie-1 and Tie-2 comprise the Tie family of RTKs and share the angiopoietins as activating ligands. Tie-1 is typically expressed on vascular endothelium and has been implicated in tumor angiogenesis [40]. Expression of Tie-1 has been reported in breast, gastric, colon, and thyroid cancers, but constitutive activation has only been proven in a breast cancer cell line [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Tie-1 is typically expressed on vascular endothelium and has been implicated in tumor angiogenesis [40]. Expression of Tie-1 has been reported in breast, gastric, colon, and thyroid cancers, but constitutive activation has only been proven in a breast cancer cell line [40,41]. In a study of 135 patients with TC, Tie-1 immunoreactivity was observed in PTC and anaplastic TC but not FTC or follicular adenomas, and it was also noted that large tumors had decreased expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Also in gastric carcinoma, Ang‐2 was expressed not only in endothelial cells but also in cancer cells, suggesting an Ang‐2‐Tie2 extravascular signalling together with Ang‐1‐Tie2 signalling [130]. Tie1 is expressed and constitutively phosphorylated to induce downstream signals in cancer cells of the breast, thyroid and gastrointestinal tract and in tumour cell line [131]. There is very little information on Ang‐1‐Tie2 signalling in cancer, outside the vasculature.…”
Section: Ang‐1‐tie2 and Cancermentioning
confidence: 99%
“…2006). Tie1 mRNA expression is increased in breast tumours, and while Tie1 expression and activation have been reported in MCF‐7 and inflammatory human breast cancer cell lines in vitro (Rees et al. 2007) (Shirakawa et al.…”
Section: Discussionmentioning
confidence: 99%